Developmental Fairy Tales - Jones, Andrew F. (Harvard University Press, 2011)
In 1992 Deng Xiaoping famously declared,
10.4159/harvard.9780674061033
Keywords: Chinese literature / History and criticism; Chinese literature; Fairy tales / China / History and criticism; Fairy tales; Literatur in anderen Sprachen; Literature and society / China; Literature and society; Modernism (Literature); Modernism (Literature) / China; LITERARY CRITICISM / Asian / Chinese